Students’ experiences and perceptions of the habit of staying up late - Nugroho, Egidius Christianto; Daeli, Kluit Ferrieli; Wicaksono, Benedictus Satrio Adi; Wijayanti, Lucia Wiwid (Proceedings of International Conference on Research in Education, 2025)
A person can be considered responsible if they consciously and intentionally do things that have a positive impact on the body. Unfortunately, in today’s modern era, staying up late or sleeping late is a habit considered common among college students. This literature review aims to explore students’ experiences and views on the habit of staying up late, identify its impacts on physical and mental health as well as academic activities, and formulate strategies for improving healthy lifestyle behaviors in an effort to reduce or avoid the habit of staying up late. This literature review method consists of the collection, examination, and objective analysis of data regarding the habit of staying up late in college students. The results of the literature review reveal that staying up late in college is influenced by academic demands, social activities, and ineffective time management patterns, which can disrupt sleep cycles, reduce productivity, increase the risk of emotional disorders, and worsen concentration. The findings indicate that the habit of staying up late has a significant impact on students’ well-being, both physically and mentally.